Haplotypes in CCR5-CCR2, CCL3 and CCL5 are associated with natural resistance to HIV-1 infection in a Colombian cohort (2017)
ABSTRACT: ntroduction: Variants in genes encoding for HIV-1 co-receptors and their natural ligands have been individually associated to natural resistance to HIV-1 infection. However, the simultaneous presence of these variants has been poorly studied.Objective: To evaluate the association of single and multilocus haplotypes in genes coding for the viral co-receptors CCR5 and CCR2, and their ligands CCL3 and CCL5, with resistance or susceptibility to HIV-1 infection.Materials and methods: Nine variants in CCR5-CCR2, two SNPs in CCL3 and two in CCL5 were genotyped by PCR-RFLP in 35 seropositive (cases) and 49 HIV-1-exposed seronegative Colombian individuals (controls). Haplotypes were inferred using the Arlequin software, and their frequency in individual or combined loci was compared between cases and controls by the chi-square test. A p’ value <0.05 after Bonferroni correction was considered significant.Results: Homozygosis of the human haplogroup (HH) E was absent in controls and frequent in cases, showing a tendency to susceptibility. The haplotypes C-C and T-T in CCL3 were associated with susceptibility (p’=0.016) and resistance (p’<0.0001) to HIV-1 infection, respectively. Finally, in multilocus analysis, the haplotype combinations formed by HHC in CCR5-CCR2, T-T in CCL3 and G-C in CCL5were associated with resistance (p’=0.006).Conclusion: Our results suggest that specific combinations of variants in genes from the same signaling pathway can define an HIV-1 resistant phenotype. Despite our small sample size, our statistically significant associations suggest strong effects; however, these results should be further validated in larger cohorts.